The Development of Regional Sports Policy to Support National Sports Achievements - Andi Nova; Soegiyanto Soegiyanto; Bambang Budi Raharjo; Irwan Budiono (Universitas Negeri Semarang, 2021)
National sports development ought to integrate regional and central government policies in order to implement the policies. Sports development policies lead to sports for everyone, talent scouting, and sports coaching sustainably. Every region in Indonesia has regional autonomy to implement sports development policies as stated in the Law of National Sports System( SKN 2005). Regional sports development policies improve national sports by focusing on introducing and involving society massively, talent scouting, and sports coaching, then each region can be summed up as its domain sports. Improving and developing national sports achievements as a result of regional sports policies would create a new competitive generation so that they can encourage national sports achievements at the international level.